An investigation into the effect of longitudinal micro-striations and their profiles, on the drag of flat plates - Parker, Kamalluddien (Department of Mechanical Engineering, 2016)
This report describes an investigation into the use of streamwise-machined grooves as a means of reducing the drag force experienced by a flat plate. V-grooves of specific dimensions are machined onto the surface of a smooth plate, in a streamwise direction. The effect of these surface modifications on the drag force of a smooth plate is examined. The use of surface modifications as a means of reducing viscous drag on a body has potential aerodynamic and hydrodynamic applications. The idea that a longitudinally grooved surface ("riblets") could reduce the turbulent skin friction developed in part from the concept that the scales of fast-swimming sharks may have a surface structure that improves boundary-layer performance. Previously conducted experiments show that v-grooves parallel to the airflow reduce drag by 4 to 7 percent. Reduced aerodynamic drag in aircraft for example, translates into reduced engine power required to overcome the drag and ultimately to lower fuel consumption. The initial part of this thesis, which dealt with the assimilation of information regarding previous riblet research, indicated that riblets with av-groove or triangular geometry had shown the greatest potential for use as a drag reducing mechanism. The experimental part of this thesis explores two possible riblet geometries. The performance of a symmetric and unsymmetrical v-groove pattern is investigated.